Priapism – we need to act fast. Definition, diagnosis and management - Przemysław Gorczyca; Agnieszka Borowiec; Kinga Borowiec (Quality in Sport)
Priapism refers to a prolonged erection caused by dysfunction in the mechanisms that control penile tumescence, rigidity, and flaccidity. An accurate diagnosis of priapism is urgent and requires identifying the underlying hemodynamic causes. The aim of this study is to identify the different types of priapism, examine its pathogenesis and epidemiology, and to present evidence-based guidelines for effective management. A thorough review of the current guidelines and relevant literature was conducted. The articles with the highest level of evidence were chosen. Swift diagnosis and effective management of priapism are crucial to prevent unnecessary interventions and ensure the best possible outcomes for erectile function.